2014
DOI: 10.1186/s12941-014-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of pomegranate peel extract and isolated compound punicalagin against dermatophytes

Abstract: BackgroundDermatophyte species infect the epidermis and appendages, often with serious social and health-economic consequences. The hydroalcoholic extract of pomegranate fruit peel showed activity against the dermatophyte fungi Trichophyton mentagrophytes, T. rubrum, Microsporum canis and M. gypseum.MethodsHydroalcoholic extract was prepared with pomegranate peels. This crude extract was fractionated and submitted to liquid-liquid partition, resulting in an active fraction which was fractionated in a Sephadex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 25 publications
4
43
0
5
Order By: Relevance
“…In our study, ethanol 80% extract of pomegranate fruit peels showed antifungal activity against isolated dermatophytes; Trichophyton mentagrophyte 1, Trichophyton verrecusom, Trichophyton terrestre, Trichophyton mentagrophytes 2 and Microsporum boullardii but no activity was recorded on Microsporum gypseum. The results were in a close agreement with that of Foss et al, (2014) and Barathikannan et al, (2016) who reported that hydroalcoholic and alcoholic extract of pomegranate fruit peels showed activity against the dermatophytes Trichophyton mentagrophytes, Trichophyton rubrum, Microsporum canis, and Microsporum gypseum. Mahajan et al, (2014); Khaleel et al, (2016); Mohammed et al, (2016); Akroum, (2017); Mostafa et al, (2017); Rosas-Burgos et al, (2017) The present study showed that hexane, ethyl acetate, and 80% ethanol extracts of fennel fruits did not affect the tested fungi.…”
Section: Determination Of the Active Components Of The Potent Extractssupporting
confidence: 92%
“…In our study, ethanol 80% extract of pomegranate fruit peels showed antifungal activity against isolated dermatophytes; Trichophyton mentagrophyte 1, Trichophyton verrecusom, Trichophyton terrestre, Trichophyton mentagrophytes 2 and Microsporum boullardii but no activity was recorded on Microsporum gypseum. The results were in a close agreement with that of Foss et al, (2014) and Barathikannan et al, (2016) who reported that hydroalcoholic and alcoholic extract of pomegranate fruit peels showed activity against the dermatophytes Trichophyton mentagrophytes, Trichophyton rubrum, Microsporum canis, and Microsporum gypseum. Mahajan et al, (2014); Khaleel et al, (2016); Mohammed et al, (2016); Akroum, (2017); Mostafa et al, (2017); Rosas-Burgos et al, (2017) The present study showed that hexane, ethyl acetate, and 80% ethanol extracts of fennel fruits did not affect the tested fungi.…”
Section: Determination Of the Active Components Of The Potent Extractssupporting
confidence: 92%
“…Tabaraki et al (2012) described the application of 70 % aqueous EtOH for extracting pomegranate peel at 60°C temperature for 30 min. Foss et al (2014) employed 90 % hydroalcoholic solution to extract pomegranate peel at room temperature for 5 days extraction. The use of EtOH in combination with water could probably bring about higher order of damage to the peel tissue than caused by individual components.…”
Section: Resultsmentioning
confidence: 99%
“…Pomegranate peel has also been extracted using ultrasound assisted extraction with 70 % aqueous EtOH (Tabaraki et al 2012) at 60°C for 30 min. Foss et al (2014) employed 90 % hydroalcoholic solution at room temperature in dark for 5 days to extract pomegranate peel and studied its antifungal activity.…”
Section: Introductionmentioning
confidence: 99%
“…PoPx showed a strong broad‐spectrum AMA against Gram‐positive ( Bacillus subtilis and S. aureus ) and Gram‐negative ( E. coli and Klebsiella pneumonia ) bacteria, with MIC ranging from 0.2 to 0.78 mg mL −1 (Fawole et al ., ). The crude extract of PoP showed a good ABA against S. aureus , B. subtilis and Pseudomonas aeruginosa with MICs of 0.062, 0.062 and 0.25 mg mL −1 respectively (Foss et al ., ). ABA of PoP enhanced in combination with CuSO 4 against clinical isolates of methicillin‐resistant S. aureus (MRSA), methicillin‐sensitive S. aureus (MSSA) and Panton‐Valentine Leukocidin (PVL) positive community‐acquired methicillin‐sensitive S. aureus (CA‐MSSA) strains (Gould et al ., ).…”
Section: Antimicrobial Potential Of Pomegranate Peelsmentioning
confidence: 97%
“…AFA of PoP against fungal strains is shown in Table S2. The crude extract of PoP showed good AFA against four species of dermatophyte fungi Trichophyton mentagrophytes , T. rubrum , Microsporum canis and Microsporum gypseum with MICs of 0.125, 0.125 and 0.25 mg mL −1 respectively (Foss et al ., ). Punicalagin is a major component of PoP which acts on the conidial and hyphal structures of dermatophytes.…”
Section: Antimicrobial Potential Of Pomegranate Peelsmentioning
confidence: 97%